Development of a Land and Building Tax Monitoring Module in the North Isimu Village Information System - Risaji, Indra; Dako, Amirudin Yunus; Dako, Rahmat Dedi R.; Musa, Wahab; Bonok, Zainudin; Abdussamad, Syahrir (Jambura Journal of Electrical and Electronics Engineering, 2024)
The information system is a tool to facilitate the potential and resource management in a village. However, due to the current development of the information system in Isimu Utara Village, there are some unavailable and inaccessible features in the system, one of which is the monitoring feature for land and building tax payments. Thus, the researcher is concerned with developing new features in the village information system as one of the alternatives to overcome the problem. This research aimed to develop a land and building tax monitoring module that could be integrated into existing systems. This research implemented the Extreme Programming (XP) method because it had fast and iterative development stages for each part and was aligned with the main goals and targets of development. The result showed that the monitoring module was integrated successfully and became one of the main menus in the village information system. The result of the Unit Test and Acceptance Test also showed that the program has run well.